THE CROSS-IDENTIFICATION, VISUALIZATION AND COMPARATIVE ANALYSIS OF ASTRONOMICAL CATALOGS IN A COMMON DATABASE RADC - Kitaeva, M. A.; Samodurov, V. A.; Dumsky, D. V.; Isaev, E. A.; Pugachev, V. D. (Одеські астрономічні публікації, 2017)
The Pushchino Observatory of ASC LPI have been developing in some last years database of some astronomical catalogs (Radio Astronomy Data Center - RADC, look on http://astro.prao.ru/db/ and http://observations.prao.ru/). In the database have the most commonly used by radio astronomers data: survey catalogs of radio sources at different radio frequencies (as well as in other spectral bands), catalogs of the major sky objects studied in astronomy etc.